Effects of contact time of natural cu-zeolite on the growth of Streptococcus pyogenes and Pseudomonas aeruginosa - Erwid Fatchur Rahman; Bambang Dwirahardjo; Poerwati Soetji Rahajoe (Majalah Kedokteran Gigi Indonesia, 2020)
Infection of a surgical wound due to bacteria is a major problem for surgical patients. Cu-zeolite is a material that can suppress bacterial growth with reversible cation characteristics and adsorption to be developed into non-toxic disinfectants for humans. Packaging uses filter paper to keep disinfectant solutions or instruments that will be sterilized clean. This study aimed to observe the effects of contact time of natural Cu-zeolite on the growth of Streptococcus pyogenes (S. pyogenes) and Pseudomonas aeruginosa (P. aeruginosa) bacteria. An experimental research was simple randomized design. Cu-zeolite 10 grams were packaged in Whatman no 42 paper bags measuring 5 x 5 cm2, contacted for 15, 30 and 45 minutes in 99.5 ml of distilled water exposed to 0.5 x 108 CFU / ml of S. pyogenes and P. aeruginosa. Subsequently, bacterial growth was calculated using total plate count method. The average growth of S.pyogenes for 15, 30 and 45 minutes (1840 ± 571.236 CFU; 29 ± 16.33 CFU and 0 CFU) while P. aeruginosa was (2776 ± 725.277 CFU; 55 ± 23.214 CFU and 0 CFU) respectively. Based on the independent t-test on Cu-zeolite, the bacterial growth in the 15th and 30th minute contact between S. pyogenes and P. aeruginosa was significantly different (pth and 30th minute contact.